Culture shapes how we look: Comparison between Chinese and African university students (Journal of Eye Movement Research, 2016)
Previous cross-cultural studies find that cultures can shape how we look during scene perception, but don’t mention its condition and limited to the East and West. This study recruited Chinese and African students to testify the cultural effects on two phases. In free-viewing phase: Africans fixated more on the focal objects than Chinese, while Chinese payed more attention to the backgrounds than Africans especially on the first fourth and fifth fixations. In recognition phase, there was no cultural difference on perception, but Chinese recognized more objects than Africans. Based on chosen subjects, we conclude that cultural differences exit on scene perception under conditions of no task and more clearly in its later period, but that differences may be hidden in a deeper way (e.g. memory) in task condition.